Neurorobotic Models of Neurological Disorders: A Mini Review - Pronin, Savva; Wellacott, Liam; Pimentel, Jhielson; Moioli, Renan C.; Vargas, Patricia A. (Frontiers in Neurorobotics, 2021)
Modelling is widely used in biomedical research to gain insights into pathophysiology and treatment of neurological disorders but existing models, such as animal models and computational models, are limited in generalisability to humans and are restricted in the scope of possible experiments. Robotics offers a potential complementary modelling platform, with advantages such as embodiment and physical environmental interaction yet with easily monitored and adjustable parameters. In this review, we discuss the different types of models used in biomedical research and summarise the existing neurorobotics models of neurological disorders. We detail the pertinent findings of these robot models which would not have been possible through other modelling platforms. We also highlight the existing limitations in a wider uptake of robot models for neurological disorders and suggest future directions for the field.